Pattern of neurosurgical practice at a university hospital in KSA during COVID-19 pandemic. Issue 3 (June 2022) - Saeedi, Rothaina; Bajunaid, Khalid; Sabbagh, Abdulrahman J.; Alomar, Soha; Alyousef, Mohammed; Baeesa, Saleh S.
الملخص: أهداف البحث: تأثرت الخدمات الطبية ودخول المستشفى الاختياري بجائحة فيروس كورونا. حاولت تخصصات متعددة دراسة تأثير الوباء على خدماتهم. نهدف إلى دراسة تأثير هذا الوباء على خدمة جراحة الأعصاب في مستشفى جامعة الملك عبد العزيز بجدة على مدى ثمانية أشهر. طرق البحث: في هذه الدراسة الاستعادية لسلسلة الحالات من مركز واحد، قمنا بتضمين جميع مرضى جراحة الأعصاب الذين خضعوا لتدخل جراحي من 3 مارس 2020 إلى 3 نوفمبر 2020 لمدة 8 أشهر. تم جمع البيانات الديموغرافية للمرضى، والتشخيص، ونوع الجراحة، وفئة الأولوية، وبيانات الوفيات. النتائج: خضعت 147 حالة لعملية جراحية خلال فترة الدراسة. كان متوسطالعمر 30.8 سنة. كان 49% من مجتمع الدراسة من الرجال. كانت حالات الأورام وموه الرأس أعلى عدد من الحالات بنسبة 31.3٪ و 23.8٪ على التوالي. وكان أكثر من نصف الحالات قضايا ذات الأولوية الأولى (عاجلة وخلال 24 ساعة). وبلغ معدل الوفيات 4.1٪ بين الحالات التي تم إجراؤها. الاستنتاجات: من خلال وصف هذه التجربة في جراحة الأعصاب المحلية أثناء جائحة كوفيد-19، نأمل في إظهار بعض الصعوبات التي واجهناها، وتحسين ما تعلمناه خلال الوباء الحالي. Abstract: Objective: The coronavirus disease 2019 (COVID-19) pandemic affected both medical services as well as hospital admissions. Scholars have attempted to study the effect of the pandemic on the services of multiple specialities. In this study, we aim to examine the pandemic's impact on the neurosurgical service provided at the King Abdulaziz University Hospital in Jeddah over an eight-month period. Methods: In this retrospective, single-centre case series study, we included all the consecutive neurosurgical patients who underwent a surgical intervention in the 8-month period starting on 3rd March, 2020 and ending on 3rd November, 2020. The demographics, diagnosis, surgery type, priority category, and mortality data of the patients were collected. Results: A total of 147 patients underwent surgery during the study period. The mean age was 30.8 years. Forty-nine percent of the study population were men. Oncology (31.3%) and hydrocephalus (23.8%) recorded the highest number of cases. More than half of the cases were Priority 1 (immediate and within 24 h). The mortality rate was 4.1% among all the performed cases. Conclusion: By describing this local neurosurgical experience during the COVID-19 pandemic, we hope to bring out some of the difficulties we encountered and improve what we learned during the pandemic.